Organic semiconductor design, synthesis and testing for solar energy applications - Willner, B (2024)
Renewable electricity generation, and particularly renewable H2 generation is essential to reach net-zero CO2 global emissions. This thesis explores the use of organic semiconductors to achieve these ends. Direct photocatalytic utilisation of sunlight to produce H2 from water is thought to be capable of providing the cheapest pathway to renewable H2 generation in the long term. Heterogeneous catalysis is generally enhanced by large surface areas, however thus far, introduction of porosity in organic semiconductors for photocatalytic H2 production has not reflected this. To better understand the influence of porosity and hydrophilicity, a family of conjugated intrinsically microporous polymers of varying porosities and hydrophilicities was synthesised. In Chapter 2, the variables of porosity and hydrophilicity were isolated by controlling the molecular design of the polymers. It was found that changing porosity and hydrophilicity independently when other factors are controlled leads to increases in activity. However, it is the combination of both properties that sees a synergistic benefit. It was shown through transient absorption spectroscopy (TAS), that two of the pure porous conjugated polymers are capable of almost instantaneous polaron generation in the absence of ascorbic acid, Pt, and less than 1 ppm residual Pd. Through investigating the wetting properties of the porous materials, this was attributed to differences in the accessibility of electrolyte to the porous structures. In Chapter 3, it was shown that by balancing bulky orthogonal tert-butyl spirofluorene flanking groups, it was possible to make solution processable porous conjugated polymers. Finally in Chapter 3, the excellent tunability of organic semiconductors was applied to the design and synthesis of electron transport layers (ETLs) for perovskite solar cells. Six small molecules with frontier molecular orbitals (FMOs) in an energy cascade were synthesised. From these, the ETLs with the deepest LUMOs gave the best performances in solar cells.